Desempeño de la Planta de Tratamiento de Aguas Residuales de São João de Iracema (Brasil) - Matsumoto, Tsunao; Sánchez, Iván Andrés (Ingeniería, 2016)
Context: Some of the most important parameters measured in the sewage treatment plant –STP- are: organic matter, solids and faecal organisms. The objective of this work was to diagnose the performance of S˜ao Jo˜ao de Iracema STP for those parameters removal. Method: A batimetric survey of the anaerobic and facultative lagoons; the STP influent and effluent monitoring in three different climate seasons of 3-month long each were conducted by dissolved oxygen, pH, temperature, BOD, filtered BOD, COD, solids and coliforms measuring. Results: Sludge accumulations of 1.3 and 6.5% in the anaerobic and facultative lagoons were registered; average BOD removal was of 73.6%, smaller than the 80% recommended by Brazilian legislation; the average faecal coliform number on final effluent was of 9.55*106/100mL, above the per-missible limit of 1000/100mL. Conclusions: The STP needs to set-up a post treatment system that guarantees additional organic matter removal and fecal coliforms in order to adjust the effluent quality to the environmental legislation standards.